Addressing variability and advancing methodological clarity in plant-soil feedback experiments - Mnqobi C. Zuma; Treena I. Burgess; Sarah J. Sapsford (Journal of Plant Interactions)
Plant-soil feedbacks (PSFs) are essential for understanding plant community dynamics and ecosystem restoration. Glasshouse experiments provide controlled environments to study PSFs, but isolating biotic and abiotic influences remains challenging. Soil sterilization removes biotic components, with biotic effects restored via live inoculum. However, inconsistencies in sterilization methods, inoculum ratios, and storage practices complicate reproducibility. This literature review synthesizes 184 PSF studies from the past 24 years, to document methodological variation and reporting inconsistencies that influence experimental design, interpretation, and cross-study comparability, specifically highlighting variability in sterilization parameters and live inoculum application. Many studies overlooked nutrient flushes and persistent microbial activity post-sterilization. No consensus exists on live inoculum ratios, and storage practices remain poorly reported, limiting cross-study comparability. Reproducibility and realism in PSF estimates may be strengthened through measures including, but not limited to: (1) improved methodological reporting of core parameters, (2) validation of sterilization success, and (3) empirically determined inoculum ratios.